2012
DOI: 10.14710/bioma.14.1.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribusi Famili Zingiberaceae Pada Ketinggian Yang Berbeda Di Kabupaten Semarang

Abstract: Zingiberaceae merupakan tumbuhan obat yang menjadi komoditas unggulan. Kabupaten Semarang merupakan salah satu sentra distribusi Zingeberaceae. Faktor lingkungan yang mempengaruhi distribusi Zingiberaceae adalah ketinggian tempat, kelembaban, suhu udara, pH tanah, dan intensitas cahaya. Tujuan penelitian ini adalah untuk mengkaji jenis-jenis tumbuhan anggota Zingeberaceae, distribusi Zingiberaceae, dan pengaruh ketinggian tempat terhadap distribusi Zingiberaceae di Kabupaten Semarang. Penelitian dilaksanakan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…However, only two species of Curcuma were found to be used in Rongkong. Studies on distribution of Zingiberaceae at different altitudes in Semarang (Sari et al 2012) revealed that at places more than 1250 m above sea level, only four species found, in which C.longa and Z.officinale are not mentioned.. Another report from southern slope of Mount Merapi, Yogyakarta has also found that three most widely used botanical families were Zingiberaceae, Asteraceae, and Lamiaceae (Nahdi and Kurniawan 2019), as found in the current study of Rongkong. In Rongkong, A. cepa appears to be the most important medicinal species since it was cited in 11 remedies.…”
Section: B I O D I V E R S I T a S 21 (2): 642-651 February 2020 648supporting
confidence: 76%
“…However, only two species of Curcuma were found to be used in Rongkong. Studies on distribution of Zingiberaceae at different altitudes in Semarang (Sari et al 2012) revealed that at places more than 1250 m above sea level, only four species found, in which C.longa and Z.officinale are not mentioned.. Another report from southern slope of Mount Merapi, Yogyakarta has also found that three most widely used botanical families were Zingiberaceae, Asteraceae, and Lamiaceae (Nahdi and Kurniawan 2019), as found in the current study of Rongkong. In Rongkong, A. cepa appears to be the most important medicinal species since it was cited in 11 remedies.…”
Section: B I O D I V E R S I T a S 21 (2): 642-651 February 2020 648supporting
confidence: 76%
“…The demand for medicinal plants of the Zingiberaceae family in the herbal and pharmaceutical sectors is quite significant, owing to the community's increasing demand for medicinal plants. In their research, Sari et al (2012) stated that environmental factors such as topography greatly affect the distribution and growth of an organism. It was explained that the distribution of the Zingiberaceae plant family was affected by environmental factors and, most importantly, the community's interest and needs for Zingiberaceae plants for consumption or commerce.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Potensi ini didukung oleh ketersediaan sumber daya flora, keadaan tanah dan iklim, serta perkembangan industri obat modern dan tradisional di Indonesia. Keadaan iklim dan tanah Indonesia yang beriklim tropis menjadi salah satu keunggulan untuk pengembangan berbagai jenis famili zingiberaceae termasuk kunyit putih (Sari et al, 2012). Kandungan utama dari Kaempferia rotunda L. adalah Benzyl benzoate dan crotepoxide sebagai antibakterial yang dapat melawan bakteri (Diastuti et al, 2018).…”
Section: Pendahuluanunclassified